A Systems View of Companies' Communication in Online Social Environments. (2nd January 2017) - Caputo, Francesco; Buhnova, Barbora; Evangelista, Federica; Russo, Giuseppe
ABSTRACT: In order to enrich previous contributions interested in the identification of possible pathways to improve companies' capabilities to better face the challenges imposed by increasing social and economic variety, this paper focuses attention on the role of companies' communications in online social environments. Thanks to the adoption of systems thinking, the paper enlarges existing contributions on companies' online communication by combining the research streams of signalling theory, capital need theory, and legitimacy theory. By building on a multi-disciplinary literature review, this paper identifies three variables to analyse the effectiveness of companies' communication based on the use of social networks: the frequency, the instability, and the previous activities. Empirical research is proposed with reference to a sample composed by the 50 best performing European companies in terms of return on sales (ROS) (USD) in 2015 via the use of structural equation modelling (SEM). SEM is applied to explore the relationships among identified variables in companies' online communication on Facebook and Instagram, and how those communications influence companies' economic performance in terms of ROS.